Răspuns :
(x+2)³ - (x+2) = (x+1)(x+2)(x+3)
(x+2)[ (x+2)² - 1 ] = (x+1)(x+2)(x+3)
(x+2)( x² + 4x + 4 - 1 ) = (x+1)(x+2)(x+3)
(x+2)( x² + 4x + 3 ) = (x+1)(x+2)(x+3)
(x+2)( x² + 3x + x + 3 ) = (x+1)(x+2)(x+3)
(x+2)[ x(x+3) + (x+3) ] = (x+1)(x+2)(x+3)
(x+2)(x+3)(x+1) = (x+1)(x+2)(x+3) , adevarat pentru orice x numar real.
(x+2)[ (x+2)² - 1 ] = (x+1)(x+2)(x+3)
(x+2)( x² + 4x + 4 - 1 ) = (x+1)(x+2)(x+3)
(x+2)( x² + 4x + 3 ) = (x+1)(x+2)(x+3)
(x+2)( x² + 3x + x + 3 ) = (x+1)(x+2)(x+3)
(x+2)[ x(x+3) + (x+3) ] = (x+1)(x+2)(x+3)
(x+2)(x+3)(x+1) = (x+1)(x+2)(x+3) , adevarat pentru orice x numar real.
(X+2)(X+2)(X+2)-(X+2)=
(X+2) FACTOR COMUN·( (X+2)(X+2)-1 )=
(X+2)·(X·X+4X+4-1)=
(X+2)(X·X+4X+3)=(X+2)(X+3)(X+1)= CU CE AU SPUS EI
(X+2) FACTOR COMUN·( (X+2)(X+2)-1 )=
(X+2)·(X·X+4X+4-1)=
(X+2)(X·X+4X+3)=(X+2)(X+3)(X+1)= CU CE AU SPUS EI